Hydraulic performance of a reed bed/freezing bed technology for septage dewatering. Issue 1 (17th October 2017) - Kinsley, Christopher; Kennedy, Kevin; Crolla, Anna
Abstract : The combined application of sludge treatment reed bed and freezing bed technology has been demonstrated to effectively dewater septage year-round under cold climate conditions in a 5-year field scale trial. Solid and hydraulic loading rates were varied from 43 to 147 kg total solids (TS)/m 2 /year and 1·9 to 5·9 m/year to two 187 m 2 planted and one 187 m 2 unplanted systems. Winter freeze–thaw conditioning was shown to consistently double filter drainage rates in spring compared with summer operating conditions at equivalent hydraulic head, indicating that freeze–thaw conditioning can restore bed hydraulic conductivity and mitigate the risk of clogging. No significant effect on system drainage was observed between planted and unplanted systems, between 7 and 21 d of dosing cycles or with solid loading rates between 49 and 144 kg TS/m 2 /year. However, drainage rates were shown to vary significantly with the hydraulic loading rate. A design loading rate of 2·9 m/year is recommended for septage treatment in reed bed systems operating in cold climates.